A stochastic programming model for multi-product oriented multi-channel component replenishment. (August 2015) - Zhen, Lu; Wang, Kai
Abstract: Assemble-to-order (ATO) manufacturing companies face decision problems on components replenishment and outsourcing channels adoption. This paper proposes a stochastic programming approach on component replenishment decisions for an ATO contract manufacturer who faces a single period stochastic demand for multiple products made by multiple components. The first stage of the proposed model is to decide the quantities for pre-stocking all types of components. After the confirmation of the demands, the second stage is to decide the quantities of outsourcing components and the outsourcing channels among several candidates for each component. In addition, the assignment of components to the productions of different products, and the decreasing trends of products׳ prices with respect to their delivery time are considered. For the problem, this paper proposes a stochastic programming model. The nonlinear objective is linearized by some approximation. For solving the model, a local branching based solution method is suggested. Some numerical experiments are performed to investigate the efficiency of the proposed solution method and the effectiveness of the proposed model.